Oral to literary: kvöldvaka, textual instability, and all that jazz - Allard, Joe (Universität Tübingen, 2004)
Saga entertainment (sagnaskemtun) was a regular element of any social gathering in medieval Scandinavia (cf Þorgils saga ok Hafliða; Íslendings þáttur sögufróða;Stjörnu-Odda draumr, etc.). Many studies of the old literature suggest that the eleventh and twelfth centuries witness a shift in the practice and mode of learning in Iceland from a dominantly oral tradition to a dominantly literate and literary one. With the invention and development of a method of writing Old Norse/Icelandic after the advent of Christianity, Icelanders with the new technology gradually became the dominant voice. Our critical and scholarly positions in the last century don’t deny the vigour or importance of the oral tradition, but since our business has been about words on the page, we have found it difficult to say very much about orality in practice. In many recent discussions of the oral tradition and the newer literary tradition is has been assumed that the literary gradually replaced the oral; that sagas increasingly were ‘read’ from texts, rather than recited from memory; and if recited from memory had been learned from texts ( Foote, Pálsson, Lönnroth, Goody etc). My paper argues that several modes of performance co-existed from very early on in Iceland’s history, and that a particular kind of improvisational oral pattern was certainly one of them. Amongst other examples I will consider Halldor Snorrason’s position as a teller of tales in the saga tradition, and reflect upon Jón Karl Helgason’s observations about the evolution of the ‘truth’, in an oral transmission, about the burning of Njal and his family (in The Rewriting of Njal’s Saga). Finally I will use several of the inconsistencies, narrative shifts and poor poetry in Stjörnu-Odda draumr to argue that, like jazz as opposed to score-based classical music, there are motifs and techniques in the recorded version of the þáttur that reveal its originally oral and improvisational nature.